Effect of thermal buoyancy on flow pattern from a pair of side-by-side confined triangular cylinders (Bangladesh Journal of Scientific and Industrial Research, 2020)
The effects of ax ial and radial thermal buoyancy on fluid flow and mixed convection heat transfer from a pair of identical triangular cylinders in side-by-side arrangement confined within a straight channel. The numerical simulations are carried out by solving continuity, momentum and energy equations using the commercial code ANSYS-CFX. The obtained results are presented and discussed within the range of following conditions: Richardson number Ri = 0 to 2, Reynolds Re = 20, and Prandtl number Pr = 1 at fixed value of blockage ratio β = 0.2. The main results are depicted in terms of streamline and isotherm contours to analyze the fluidic and energetic behaviors. The total drag coefficient and average Nusselt number are also computed. Moreover, a simple correlation indicating the variations of drag coefficient and average Nusselt number versus Richardson number are also provided. It was found that for axial effect of thermal buoyancy, increase in buoyancy strength enhances the heat transfer rate for both cylinders. In other hand, for radial effect, increase in buoyancy strength increases the heat transfer rate of down cylinder and it is reduced for the upper cylinder.Bangladesh J. Sci. Ind. Res.55(1), 9-14, 2020